Technology, management and business : evolving perspectives - Misra, Rajnish Kumar; Shrivastava, Archana; Sijoria, Charu (Emerald Publishing Limited, 2023)
Advanced Series in Management: Volume 31 offers cutting-edge research from an international range of academics, who engage with the potential opportunities and challenges of digitization in the workplace. Contributors introduce fresh evidence and innovative ideas on the changing work environment to help business leaders shift to the digital mind-set. The book will throw light on what manufacturers, retailers, marketer brands, and consumers can do to secure value; digitally transform and/or innovate themselves in terms of design, production, and distribution as they move towards "next normal" business practices. Technology, Management and Business: Evolving Perspectives provides researchers, academicians, policymakers and professionals working in manufacturing, retail and consumer markets with a platform to uncover their experiences as they meet these challenges in various verticals of industry around the world.
Keywords: Work environment -- Technological innovations.; Business & Economics -- Management.; Management & management techniques.; elektronické knihy; electronic books